The Influence of Baby Massage on The Frequency and Duration of Breastfeeding in Infants Aged 0-6 Months - Wahyuni, Wahyuni; Mariza, Ana; Riyanti, Riyanti; Yantina, Yuli (Universitas Malahayati, 2024)
ABSTRACT The duration and frequency of breastfeeding in infants not only affects the infants but also their mothers, as the frequency of infant suckling influences maternal breast milk production. Data obtained from Suoh Village, the working area of the Bandar Negeri Suoh Health Center, revealed that 40% of infants were breastfeeding only 6-7 times a day, and 20% of infants were breastfeeding for just 5 minutes. One effort that can be made to increase the duration and frequency of breastfeeding is by providing infant massage therapy. The objective of this research is to determine the effect of infant massage on the frequency and duration of breastfeeding in infants aged 0-6 months in Suoh Village, the working area of Bandar Negeri Suoh Public Health Center, in the year 2023. This research employed a quantitative approach with a pre-experimental design and a one-group pretest and posttest design. The population in this study consisted of all infants aged 0-6 months in the working area of Bandar Negeri Suoh Public Health Center, with a sample size of 30 individuals. The sampling technique used was purposive sampling. The study was conducted in July 2023. The data analysis in this study employed the Wilcoxon test. The results of this study indicated that the average frequency of breastfeeding before infant massage therapy was 6.93 times, and after the therapy it increased to 10.37 times. The average duration of breastfeeding before infant massage therapy was 6.77 minutes, and after the therapy it was 10.27 minutes. The bivariate analysis results revealed that there was a significant effect of infant massage therapy on the frequency of breastfeeding with a p-value of 0.000. There was also a significant effect of infant massage therapy on the duration of breastfeeding with a p-value of 0.000. Anthe effect of infant massage on the frequency and duration of breastfeeding in infants aged 0-6 months in Suoh Village, the working area of Bandar Negeri Suoh Public Health Center, in the year 2023. Keywords: Breastfeeding Duration, Breastfeeding Frequency, Infant Massage